Brown Adipose Tissue: Activation and Metabolism in Humans - Hachemi Imane; U-Din Mueez (KOREAN ENDOCRINE SOC, 2025)
Brown adipose tissue (BAT) is a thermogenic organ contributing to non-shivering thermogenesis. BAT becomes active under cold stress via sympathetic nervous system activation. However, recent evidence has suggested that BAT may also be active at thermo-neutrality and in a postprandial state. BAT has superior energy dissipation capacity compared to white adipose tissue (WAT) and muscles. Thus, it has been proposed that the recruitment and activation of additional BAT may increase the overall energy-expending capacity in humans, potentially improving current whole-body weight management strategies. Nutrition plays a central role in obesi-ty and weight management. Thus, this review discusses human studies describing BAT hyper-metabolism after dietary interventions. Nutritional agents that can potentially recruit brown adipocytes via the process of BAT-WAT transdifferentiation are also discussed.